2023
DOI: 10.1123/jcsp.2021-0039
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Emotional Exhaustion in Professional and Semiprofessional Coaches

Abstract: The present study examined levels of emotional exhaustion, a key symptom of burnout, in Swedish professional and semiprofessional sport coaches in comparison to the normative values specified in the Maslach Burnout Inventory manual, and to the clinical cutoffs developed by Kleijweg, Verbraak, and Van Dijk. The sample contained 318 Swedish coaches (Mage = 42.7 years, 12% female) working at least 50% full time away from both team (60%) and individual (40%) sports. Our study shows that, in general, coaches in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The included studies reported heterogeneous rates of burnout. The results ranged from low [83,93,96,[104][105][106], to moderate [83,99,101,105], to high [99] levels of emotional exhaustion, depersonalisation and personal accomplishment. These findings were predominantly measured using a version of the Maslach Burnout Inventory (MBI), including a non-specified version (n = 9) [78-80, 89, 101, 102, 104-106], the MBI-General Scale (MBI-GS) (n = 4) [87,88,93,96], MBI-Educators Survey (MBI-ES) (n = 2) [98,99] and MBI-Coach (MBI-C) survey (n = 1) [83].…”
Section: Burnoutmentioning
confidence: 99%
“…The included studies reported heterogeneous rates of burnout. The results ranged from low [83,93,96,[104][105][106], to moderate [83,99,101,105], to high [99] levels of emotional exhaustion, depersonalisation and personal accomplishment. These findings were predominantly measured using a version of the Maslach Burnout Inventory (MBI), including a non-specified version (n = 9) [78-80, 89, 101, 102, 104-106], the MBI-General Scale (MBI-GS) (n = 4) [87,88,93,96], MBI-Educators Survey (MBI-ES) (n = 2) [98,99] and MBI-Coach (MBI-C) survey (n = 1) [83].…”
Section: Burnoutmentioning
confidence: 99%
“…The studies reported heterogeneous rates of burnout. The results ranged from low [83, 93,96,[104][105][106], to moderate [83, 99,101,105], to high [99] the Coach Burnout Questionnaire (CBQ) (n = 1) [103] and Coach Burnout Affect Survey (n = 1) [107]. In addition to quantitative measures, 5 studies also utilised semi-structured interviews to explore burnout [45,83,97,98,100].…”
Section: Burnoutmentioning
confidence: 99%